Climate-induced risk for the preservation of paper collections: Comparative study among three historic libraries in Italy. (December 2021) - Verticchio, Elena; Frasca, Francesca; Bertolin, Chiara; Siani, Anna Maria
Abstract: The conservation of historic libraries can be referred towards both the ancient book collections and the buildings themselves. Heritage collections made of paper are threaten by climate-induced deterioration risks such as cellulose hydrolysis. Several studies have investigated the microclimate inside historic libraries but comparisons are difficult due to the lack of long-term microclimate observations and uniformity in the use of standards and risk assessment methods. For the first time, the long-term microclimate observations collected in three historic libraries in Italy were comparatively studied to outline differences and similarities of their microclimates in terms of paper preservation. A multidisciplinary approach was applied to assess the building performance (a) and the deterioration risks for the collections (b). As for a), a common feature of the libraries was the high thermal inertia and low indoor-outdoor air exchanges. As for b), the Time Weighted Expected Lifetime (TWEL) was defined to account for an average chemical risk on a seasonal and yearly basis. TWEL allowed to highlight the impact of the most adverse conditions on the overall chemical risk for acidic paper preservation (e.g., temperatures above 20 °C reached naturally in summer/artificially in winter). It resulted that the measured microclimate conditions in the libraries would lead to the loss of their acidic collections in less than 300 years. Demographic plots were finally used to inform about the risk resulting from the synergy between handling and microclimate as well as to explore the effectiveness of possible preservation measures such as the deacidification of 10% of the collections. Graphical abstract: Image 1 Highlights: The long-term microclimate data in three historic libraries in Italy are comparatively studied. The investigation includes microclimate characterisation and conservation risk assessment. A multidisciplinary approach is used to evaluate building performance and paper deterioration. The current microclimate in the libraries reduces the expected lifetime of acidic collections. Restoration interventions might not be effective if the current microclimate is maintained.